Peningkatkan Pemahaman Konsep Matematis Peserta Didik Melalui Model Problem Based Learning Berbantuan LKPD Berbasis TaRL - Ardiasa, Athalla; Rasiman; Harun, Lukman; Heni Setiowati (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2024)
This research is classroom action research which aims to improve students’ ability to understand mathematical concepts through PBL (Problem Based Learning) learning assisted by TaRL (Teaching at the Right Level) based LKPD on opportunity material. This research was carried out at SMA Negeri 8 Semarang for the 2023/2024 academic year with the research subjects being class This research consists of two cycles. Data collection techniques are carried out through documentation of initial ability scores (pre-test), observation, and learning outcomes tests (post-test). Observations are carried out at each meeting during the learning process, including observing student activities. Learning outcomes tests are given at the end of each cycle. The results of research in cycle I showed that the average student learning outcome value increased by 14.22 from the basic value of 60.89 to 75.11. In cycle II, the average value of student learning outcomes increased by 5.09 from the value of learning outcomes in cycle I, namely 75.11 to 80.2. Student activities in cycle I were classified as sufficient and in cycle II were classified as very good. Based on the results of data analysis, it can be concluded that the PBL (Problem Based Learning) learning model assisted by LKPD based on TaRL (Teaching at the Right Level) can improve mathematics learning outcomes in class XI 3 student opportunities at SMA Negeri 8 Semarang for the 2023/2024 academic year.